(untitled) (Global Journal of Management and Business Research, 2020)
Investments are essential as the growth of the stock market denoted through increased investments results in the growth of the economy. But they are always subject to various risks in the market. These risks are to be mitigated for the development of an efficient economic system by the market itself. Apart from the stock segment, the Indian financial market is a home for futures and options segments that facilitate the hedging of risks involved in the investments. For considering any derivative market as a hedging tool, one of the prerequisites is the presence of integration between such derivative market and its underlying market. The present study focuses on testing the relationship between Indian stock market and the options market, represented by NSE Nifty 50 index and index options on it respectively, to know whether the options segment is suitable for hedging the risks implicit with investments in the stock market, with substantial consideration to payoff structure of the market denoted by different moneyness groups viz.